Relationship between sociotropy autonomy personality traits, interpersonal sensitivity and facebook addiction in nursing students - Baysan Arabacı, Leyla; Taş, Gülsenay; Kavaslar, İbrahim; Dikmen, Merve; Teke, Cemile (Journal of Dependence, 2017)
Objective: Study was conducted to determine the relationship between sociotropy and autonomy personality traits and interpersonal sensitivity and facebook addiction in university students.Material and Method: This descriptive-correlational study was conducted with 530 nursing students in 47 different universities. Data collected with "Introductory Information form ","Facebook Addiction Scale","Interpersonal Sensitivity Scale"and"Sociotropy-Autonomy Scale”.Results:. Students stated that they use internet on average 3.9 ± 2.98 hours per day, 58.1%(n = 245) has facebook account more than five years, 51.1%(n = 217) had more than one visit per day and 57.4%(n = 242) use facebook at least fifteen minutes per day. Facebook addiction scale mean-point increase when other subscales of Interpersonal Sensitivity Scale’s (interpersonal worry and dependency and low selfesteem) and the total point of scale increase.In addition, it has been determined ıf the frequency of facebook usage and the duration of daily use increases, the average scores of facebook addiction scale and Interpersonal Sensitivity scale's subscale of low self-esteem also increase.Conclusion: Nursing students facebook addiction is lower and tend to increase if interpersonal sensitivity (specially interpersonal worry and dependency and low self-esteem tendencies) increase.
Keywords: Substance abuse and problem solving; etiology of substance abuse